La Guadeloupe, ses enfants célèbres : Léonard, Lethière, Bernard, Poirié St-AurèleTT - - Vauchelet, Emile (1830-1913) (A. Challamel, 1894)
Biographie et écrits de Léonard, Lethière, Bernard et, Poirié St-Aurèle